Multiview coding and error correction coding for 3D video over noisy channels - Vosoughi, Arash; Testoni, Vanessa; Cosman, Pamela C.; Milstein, Laurence B. (Signal processing. Image communication, 2015)
We consider the joint source–channel coding problem of stereo video transmitted over AWGN and flat Rayleigh fading channels. Multiview coding (MVC) is used to encode the source, as well as a type of spatial scalable MVC. Our goal is to minimize the total number of bits, which is the sum of the number of source bits and the number of forward error correction bits, under the constraints that the quality of the left and right views must each be greater than predetermined PSNR thresholds at the receiver. We first consider symmetric coding, for which the quality thresholds are equal. Following binocular suppression theory, we also consider asymmetric coding, for which the quality thresholds are unequal. The optimization problem is solved using both equal error protection (EEP) and a proposed unequal error protection (UEP) scheme. An estimate of the expected end-to-end distortion of the two views is formulated for a packetized MVC bitstream over a noisy channel. The UEP algorithm uses these estimates for packet rate allocation. Results for various scenarios, including non-scalable/scalable MVC, symmetric/asymmetric coding, and UEP/EEP, are provided for both AWGN and flat Rayleigh fading channels. The UEP bit savings compared to EEP are given, and the performances of different scenarios are compared for a set of stereo video sequences. •We address the joint source–channel coding problem of a 3D video.•Goal is to minimize number of transmitted bits subject to video quality constraints.•We consider non-scalable/spatial-scalable MVC, and symmetric/asymmetric coding.•The JSCC problem is solved using EEP and a proposed UEP approach.•Proposed UEP approach is efficient at achieving the goal when compared to EEP.